Work placement and studies. (Journal of Parents and Teachers, 2014)
This article offers a graphic about work placement and the unemployment rate depending on whether university studies or vocational training studies have been carried out.
Keywords: Labor insertion; unemployment rate; graph; university studies; vocational training.